Evaluation of an ImmunoPET Tracer for IL-12 in a Preclinical Model of Inflammatory Immune Responses - Viola, Nerissa T.; Glassbrook, James E.; Kalluri, Jhansi R.; Hackett, Justin B.; Wicker, Madison N.; Sternberg, Joshua; Gibson, Heather M. (Frontiers in Immunology, 2022)
The immune cytokine interleukin-12 (IL-12) is involved in cancer initiation and progression, autoimmunity, as well as graft versus host disease. The ability to monitor IL-12 via imaging may provide insight into various immune processes, including levels of antitumor immunity, inflammation, and infection due to its functions in immune signaling. Here, we report the development and preclinical evaluation of an antibody-based IL-12-specific positron emission tomography (PET) tracer. To mimic localized infection and stimulate IL-12 production, BALB/c mice were administered lipopolysaccharide (LPS) intramuscularly. [89Zr]Zr-DFO-αIL12 tracer was given one hour post LPS administration and PET images were taken after 5, 24, 48, and 72 hours. We observed significantly higher uptake in LPS-treated mice as compared to controls. Biodistribution of the tracer was evaluated in a separate cohort of mice, where tracer uptake was elevated in muscle, spleen, lymph nodes, and intestines after LPS administration. To evaluate the utility of [89Zr]Zr-DFO-αIL12 as an indicator of antigen presenting cell activation after cancer immunotherapy, we compared PET imaging with and without intratumoral delivery of oncolytic adenovirus expressing granulocyte-macrophage colony-stimulating factor (Adv/GM-CSF), which we have shown promotes anti-tumor immunity. BALB/c mice were inoculated orthotopically with the mouse mammary carcinoma line TUBO. Once TUBO tumors reached a volume of ~50 mm3, mice were treated with either three intratumoral injections of 108 PFU Adv/GM-CSF or vehicle control, given every other day. Upon the last dose, [89Zr]Zr-DFO-αIL12 was injected intravenously and 72 hours later all mice were imaged via PET. Tumor-specific uptake of [89Zr]Zr-DFO-αIL12 was higher in Adv/GM-CSF treated mice versus controls. Tissues were harvested after imaging, and elevated levels of macrophages and CD8+ Tc cells were detected in Adv/GM-CSF treated tumors by immunohistochemistry. We validated that IL-12 expression was induced after Adv/GM-CSF by qRT-PCR. Importantly, expression of genes activated by IL-12 (IFNγ, TNFα, and IL-18) were unaffected after IL-12 imaging relative to mice receiving an IgG control tracer, suggesting the tracer antibody does not significantly disrupt signaling. Our results indicate that targeting soluble cytokines such as IL-12 by PET imaging with antibody tracers may serve as a noninvasive method to evaluate the function of the immune milieu in situ.